Local Magnetic Activity Index Nowcast Based on Concurrent Measurements at Two Observatories in Close Proximity - Tobias G. W. Verhulst; Stephan Bracke; François Humbled; Stanimir M. Stankov (Space Weather)
Abstract Permanent monitoring and real‐time indexing of the geomagnetic activity is of utmost importance for space weather services. In particular, providing a continuous and reliable local magnetic activity nowcast is of increasing importance as it can be used to generate alerts for various users, for instance for GNSS‐based applications or to protect electric power grids. This study presents a novel nowcast system for calculating a K‐type index of the local magnetic activity in Belgium. This includes a fully automated computer procedure for digital magnetogram data acquisition, data cleaning, calculating the index, displaying the results, and possibly issuing an alert to interested users, if the storm‐level activity is identified. Novel characteristics are the higher cadence of index calculation, an index reliability estimate based on data quality, and the high availability of the nowcast guaranteed by the operation of two identical instruments at observatories in close proximity. An evaluation of the index nowcast accuracy was carried out, and its results are also presented.